Predictors of tuberculosis among patients attending government hospitals in Yobe State, Nigeria - Mustapha, Mustapha Yannabe (2015)
Background: Numerous factors attribute to the development of tuberculosis infection however there are few studies that address the predictors of tuberculosis in Nigeria. Currently there is no research incorporating knowledge and attitude as predictors for acquiring TB among tuberculosis patients in Yobe. Objectives: To determine the predictors of tuberculosis among cases and controls attending government hospitals. Method: This is a case – control study. A case was defined as individual age 18-75 years with at least two positive sputum smears for mycobacterium tuberculosis. Systematic sampling was used to select cases. Control was defined as individual age 18-75 years attending the selected hospitals without clinical evidence of active TB. Controls were selected using simple random sampling. Self-administered questionnaire was administered to obtain information about socio-demographic characteristics, medical history, lifestyle behaviors, knowledge and attitude of the respondents about TB. SPSS version 21 was used to analyze data. Chi Square test was conducted to determine association between the cases and controls and logistic regression model (enter method) was employed to examine the predictors of TB. Results: There were 346 patients with 173 cases and 173 controls in this study. Bivariate analysis showed that there were significant association between tuberculosis cases and controls regarding sociodemograhic variables, HIV status, previous tuberculosis experience, history of contact with tuberculosis patient, smoking,knowledge and attitude towards tuberculosis. Predictors of tuberculosis included being male (AOR 3.761, 95%CI:1.794 – 7.882), income per month ₦ 1,000 – 9,000 (US$ 5 – 45) (AOR 5.791, 95%CI: 2.409 – 13.922), unemployment (AOR 4.918, 95%CI: 2.233 – 10.831), rural area (AOR 3.146, 95%CI: 1.564 – 6.328), HIV/AIDS (AOR 36.483,95%CI: 5.360 – 248.338), previous TB experience (AOR 18.398, 95%CI: 3.101 – 109.159), history of contact (AOR 6.769, 95%CI: 3.191 – 14.359), smoking (AOR 21.717, 95%CI: 2.958 – 159.445), low knowledge (AOR 4.769, 95%CI: 2.312 – 9.838) and negative attitude (AOR 2.960, 95%CI: 1.448 – 6.049). Conclusion: Being male, earning between ₦ 1,000 – 9,000 (US$ 5- 45) per month,having low education, living in rural area, HIV/AIDS, previous TB experiences and history of contact with TB patients were important predictors among TB patients. Others include smoking, low knowledge and negative attitude levels were considered significant predictors in the study. The existing study justifies that proper health education to be incorporated as part of modern tuberculosis control programme in the state.